ANALISIS GAYA BELAJAR SISWA YANG MAIN GAME ONLINE DI SEKOLAH DASAR NEGERI 010 KECAMATAN KUBU TAHUN PELAJARAN 2013/2014 - Asyari, Abu Asyari Abu; ', Nurhayati; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This study, entitled "Analysis of Student Learning Styles Play Games Online at State Primary School 010 Kubu district academic year 2013/2014". This study aims to: 1). To describe the visual learning style of students, 2). To know the description of auditory learning styles of students, 3). To find a picture of kinesthetic learning styles of students and 4). To find a picture of the students' learning styles play the game online at SDN 010 Kubu district. The method used in this research: descriptive methods. The population in this study were all students of class IV, V, and VI Elementary School 010 Kubu district school year 2013/2014, this study uses saturated sample technique or the total sample with a total sample of 92 people. The experiment was conducted in March and ending in May 2014. Based on the research results, it can be seen that the description of a visual learning style of students in middle category is 70.65%. While the picture of auditory learning style in middle category, namely 56, 57% and kinesthetic learning style picture also in middle category, namely 65, 21%, As well as an overview of learning styles of students who play online games in SD Negeri 010 Kubu district school year 2013/2014 is most of the students have a visual learning style that is 52.45% (48 people). Auditory 25.61% (as many as 24 people) and Kinesthetic 21.94% (20 persons). Based on the results of the data analysis of research, discussion, research findings, the conclusions of this study then recommended to the school (principal) Elementary School 010 Kubu district to be able to understand and care about the learning styles of students who play the game online. Expected to classroom teachers in order to further increase its attention to students' learning styles and find a method of learning that fit each student's learning style appropriately. For parents are expected to be able to accompany her home learning activities, especially for children who have unique learning styles according to the character of the child, so that the learning objectives will be easily accessible and understood the child. For researchers, the next challenge studies to investigate students' learning styles in terms of environmental and psychological factors. Keywords: Learning Styles visual, auditory and kinesthetic